2013
DOI: 10.1590/2237-6089-2013-0007
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and health comorbidities before and after bariatric surgery: a longitudinal study

Abstract: Introduction: Morbid obesity has multiple implications for psychological and physical health. Bariatric surgery has been selected as the treatment of choice for this chronic disease, despite the controversial impact of the surgery on psychosocial health. The objective of this study was to describe candidates for bariatric surgery and analyze changes in weight, psychopathology, personality, and health problems and complaints at 6-and 12-month follow-up assessments. Methods: Thirty obese patients (20 women and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…35 The authors observed an increase in conscientiousness and agreeableness, but not in openness to experience. A meta-analysis that investigated normative changes in personality traits found that conscientiousness, extraversion, and emotional stability increase at the start of adulthood.…”
Section: Changes In Personality Traits or Disorders After Bariatric Smentioning
confidence: 95%
See 4 more Smart Citations
“…35 The authors observed an increase in conscientiousness and agreeableness, but not in openness to experience. A meta-analysis that investigated normative changes in personality traits found that conscientiousness, extraversion, and emotional stability increase at the start of adulthood.…”
Section: Changes In Personality Traits or Disorders After Bariatric Smentioning
confidence: 95%
“…One study found that a reduction in markers of inflammatory processes (interleukin-6 and high sensitivity C-reactive protein) mediated the reduction in scores for anxiety and depression. 36 The extraversion factor increased in one of the studies 35 and the social anxiety factor from the DPQ reduced after the surgical procedure. Although one of the studies did not detect this change, it is possible that undergoing the surgery, and especially the weight reduction and improvement in mood symptoms, make people more likely to engage in a greater number of social relationships because they feel more confident and have higher self-esteem.…”
Section: Changes In Personality Traits or Disorders After Bariatric Smentioning
confidence: 95%
See 3 more Smart Citations